National Project, Regional Perspective: Newfoundland, Canada and Identities, 1949-1991 - Conway, Shannon (Université d'Ottawa / University of Ottawa, 2020)
The Canadian government has long striven for an official national identity grounded in a cohesive sense of national unity, but this has been in contrast to the regional reality of the Canadian state. The postwar period reveals increased concern within Canada regarding its national identity, when the federal government was attempting to construct an intrinsic identity and trying to encode what it meant to be Canadian. When Newfoundland joined Canada in 1949, it became an additional element in this enduring struggle. After confederation, a cultural revival in the province further entrenched its distinct identity during the same period in which it was acclimatizing to a new Canadian reality. The main goals of this research are to comprehend how Newfoundland understood official Canadian identity in its post-confederation period and how the province pursued a distinct identity while becoming a part of Canada. This project examines how Newfoundland understood official constructions of Canadian identity during the post-1949 period to observe how Canada’s official national identity was understood outside of the dominant central-Canada perspective. This alternative regional perspective provides an understanding of how the realities of Canada’s regionalism play a role in why the official national identity was not as homogenous or uniting as the federal government had idealized. By addressing the national question of Canadian identity through a regional Newfoundland perspective, this project seeks to deepen and expand our knowledge and understanding of modern Canada and its continued regional realities.